Strategi Pengembangan Usaha Pada Coffee Shop Int.Space Pasca Covid-19 di Kota Rangkasbitung: Business Development Strategy in Post Covid-19 Coffee Shop Int.Space in Rangkasbitung City - Saptaji, Moh Faqih Dwi; Hubeis, Musa; Zulbainarni, Nimmi (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
The National Disaster Management Agency (BNPB) aims to increase the number of patients infected with the Covid-19 virus by 20% per day. This has disrupted the economic sector in all fields, including micro, small and medium enterprises (MSMEs), one of which is the coffee shop business. This study aims to establish a Business Development Strategy to increase Coffee Shop sales in the aftermath of Covid-19. The types of data used in this study are primary and secondary data. Primary data were obtained from observations and interviews with five informants, namely Coffee Shop Int.Space Owners, Coffee Shop Int.Space Consumers, the Tourism Office in the Creative Economy Sector, Food & Beverage Consultants, and the health Office; as well as secondary data obtained from literature studies, the internet, and related institutions. This research data processing uses Strengths, Weaknesses, Opportunities, and Threats (SWOT) Analysis to determine the Strengths and Weaknesses of Coffee Shop Int.Space and then determines the right business development strategy with the QSPM (Quantitative Strategic Planning Matrix). From this analysis, recommendations for the Coffee Shop Int.Space Development Strategy are obtained, namely increasing sales through alternative product development strategies. Keywords: business development, coffee shop, covid-19, coffee marketing, msme